Struktur dan Makna dalam "Abad Tak Bermoral": Sebuah Kajian Struktural - Juli Arihta; Diana Febrianty Silalahi; Dina Olivia Sidabutar; Nila Angita Nasution; Regina Situmorang; Wahyudi Difler Rambe; Rosmawaty Harahap (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This journal analyzes the drama script "Abad Tak Bermoral" by Munief Doang using a structural approach. This study examines the theme, characters, plot, setting, style of language, and moral to understand how these elements interact with each other and form the overall meaning. Qualitative and descriptive methods are used to explore the meaning and interpretation of the script in depth. The results of the analysis show the main theme of morality and its impact on society, exploring the moral dilemmas faced by the characters. The characters have complex and diverse characters, reflecting deep internal conflicts. The storyline follows a clear narrative structure, with an introduction, conflict, climax, and resolution that provokes thought. The setting and style of language provide a strong context for the theme, while the moral invites the audience to reflect on moral values. Thus, the script "Abad Tak Bermoral" does not only function as entertainment, but also as a medium for reflection. This study is expected to contribute to a deeper understanding of structural analysis in literary works, especially in the context of modern drama.